Simulation in Neuroanesthesia: How Much to Learn? - Bhatt, Rashmi; Khanna, Puneet (Journal of Neuroanaesthesiology and Critical Care, 2018)
Taking a cue from the aviation industry, medicine took upon itself the responsibility to improve patient safety. The cause was championed by anesthesia that became a pioneer in using simulation-based training to improve the nontechnical skills, at every level of clinical training. The needs have been understood by evolving subspecialties such as neuroanesthesia as well, where a fewer number of patients and reduced margin of safety have propelled the development of simulation modules specific to requirements. The constant, ongoing advances and improvement in simulation practices have contributed immensely to the betterment of patient safety, and a significant dent in surgical morbidity and mortality probably explains why simulation-based training programs are being incorporated into teaching curriculum across the world.
Keywords: education; nontechnical skills; patient safety